2014
DOI: 10.1111/jog.12508
|View full text |Cite
|
Sign up to set email alerts
|

Fetal cardiac function measured by myocardial performance index of small‐for‐gestational age fetuses

Abstract: Aim: The aim of this study was to demonstrate the changes of right and left myocardial performance indices (MPI) in small-for-gestational age (SGA) fetuses during 28-40 weeks of gestation. Material and Methods: Singleton pregnant women during 28-40 weeks of gestation were enrolled. Estimated fetal weight was used to classify the subjects into appropriate-for-gestational age (AGA) and SGA groups. The Doppler indices of umbilical and middle cerebral arteries, including amniotic fluid index, were used to distingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
4
9
0
1
Order By: Relevance
“…Previous studies have demonstrated that pathological conditions that could influence cardiac functions also alter the Mod-MPI values. [5][6][7][8][9][10][11][12][13][14][15] In the present study, all of the UA S/D values were in the normal ranges based on GA. Therefore, we could not interpret this result objectively.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Previous studies have demonstrated that pathological conditions that could influence cardiac functions also alter the Mod-MPI values. [5][6][7][8][9][10][11][12][13][14][15] In the present study, all of the UA S/D values were in the normal ranges based on GA. Therefore, we could not interpret this result objectively.…”
Section: Discussionsupporting
confidence: 56%
“…Fetal growth restriction, twin-twin transfusion syndrome, maternal diabetes, preeclampsia, fetal hydrops, fetal anemia, and cholestasis are examples of these conditions. [5][6][7][8][9][10][11][12][13][14][15] MPI values may be a guide for fetal interference and timing of the delivery in cases that affect cardiac function. However, it is important to ensure that the measurement of MPI is consistent and accurate.…”
mentioning
confidence: 99%
“…MPI levels are expected to change in the presence of pathological conditions that influence fetal cardiac functions. These include fetal growth restriction (FGR), twin‐twin transfusion syndrome, maternal diabetes mellitus, preeclampsia, fetal hydrops, and fetal anemia . When fetal cardiac functions influence the MPI, it may be important to decide the time of the birth.…”
Section: Introductionmentioning
confidence: 99%
“…The MPI is still being investigated as a potential determinant of cardiac performance for new indications in children and adults, because of its simplicity, non‐invasiveness, straightforwardness and reproducibility . In addition, there is also reported data on the success of MPI in the prenatal period for the identification of fetal ventricular dysfunction . Moreover, the E wave/A wave peak velocity (E/A) ratio at the mitral valve was additionally defined as another tool for ventricular function analysis, but only for the diastolic component.…”
Section: Introductionmentioning
confidence: 99%